2019
DOI: 10.1108/dta-12-2018-0104
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of switching intention to cloud computing in large enterprises

Abstract: Purpose The purpose of this paper is to investigate switching intention from traditional enterprise information systems (EISs) to private cloud EIS in large enterprises. The authors propose that the factors motivate and inhibit enterprises’ switching intention to private EIS by integrating technology–organization–environment (TOE) framework and two-factor theory. Design/methodology/approach A research model draws from TOE framework and two-factor theory. Data were collected from 227 top managers and owners o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Lastly, this study also contributes methodologically, unlike previous studies which have applied SEM (Albashrawi & Motiwalla, 2020; Chang et al, 2020; Dey et al, 2020), which could only detect linear associations among the constructs. This study has gone a step ahead by applying the Artificial Intelligence tool ANN with deep architecture to cover the existing lacunas, that is, detecting both linear and non-linear associations among the studied variables.…”
Section: Implicationmentioning
confidence: 97%
“…Lastly, this study also contributes methodologically, unlike previous studies which have applied SEM (Albashrawi & Motiwalla, 2020; Chang et al, 2020; Dey et al, 2020), which could only detect linear associations among the constructs. This study has gone a step ahead by applying the Artificial Intelligence tool ANN with deep architecture to cover the existing lacunas, that is, detecting both linear and non-linear associations among the studied variables.…”
Section: Implicationmentioning
confidence: 97%
“…Internet adoption was positively significant to gaining CA by firms in diverse sectors in Singapore (Teo and Pian, 2003). Chang et al (2019) found that cloud absorptive capacity and cloud usage positively and significantly influenced CA of firms. Hence, cloud ERP adoption can enable firms gain CA.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 97%
“…As earlier explained, three unique factors of the TOE framework, FTM, TMSCM and GFS are selected as the contextual factors of cloud ERP Adoption based on prior studies' neglect of these crucial factors and Competitive advantage (CA) and organisational performance are the strategic consequences of cloud ERP adoption focused in this study, since studies have confirmed that they are the two dominant strategic benefits firms seek in IT adoption (Bruque-Camara et al, 2016;Chang, Hsu, Huang, and Chen, 2019;Lucia-Palacios et al, 2014;Shehat and Montash, 2019). These constructs are reviewed in the next section.…”
Section: Literature Review On Key Contextual Factors and Strategic Comentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is little consensus on the specification of models. For instance, researchers modeled switching costs as (1) first-order multidimensional constructs e.g., [7,13], (2) a second-order formative construct with first-order reflective constructs, e.g., [42,54], and (3) a third-order with second-order formative dimensions with first-order reflective constructs [45]. Jarvis et al [50] and MacKenzie et al [49] suggest four criteria in determining model specification: causality direction, interchangeability, covariation, and nomological net.…”
Section: Model Specificationmentioning
confidence: 99%